Exploring the stroke burden linked to Kidney dysfunction: trends, predictive insights, and health inequalities - Tang, Jiahao; Lu, Yuexin; Shi, Shunan; Wan, Shu; Wang, Ming (Frontiers in Neurology, 2025)
BackgroundOver the past 30 years, the prevalence of kidney disease has increased, underscoring the need to address the stroke burden linked to kidney dysfunction. This study aims to analyze trends and factors underlying the stroke burden and its subtypes attributable to kidney dysfunction from 1990 to 2021.MethodsIn this study, we used Global Burden of Disease data to assess stroke burden attributable to kidney dysfunction within the GBD framework. Methods included joinpoint models, decomposition analysis, age-period-cohort models, Bayesian models, and health inequality analysis.ResultsThe burden of stroke attributable to kidney dysfunction remains significant, with aging as a key factor. By 2021, such strokes caused 676.1×103 (95% CI: 467.78×103, 896.74×103) deaths and 15,009.65×103 (95% CI: 10,939.08×103, 19,133.72×103) DALYs globally. Males experience a higher burden (ASMR of 9.16 and ASDR of 200.83 per 100,000) compared to females (ASMR of 7.17 and ASDR of 150.63 per 100,000). The burden is concentrated in low SDI countries, with trends intensifying for total and ischemic strokes. Projections suggest a decline in overall burden, but an increase in ischemic stroke among younger populations.ConclusionsThe global stroke burden attributable to kidney dysfunction remains significant, with regional disparities. Public health authorities should create targeted guidelines considering economic levels, stroke subtypes, gender, and age to effectively mitigate this burden.